(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The purpose of this exploratorystudy is to examine knowledge transfer strategies within the framework of amulti-generational workforce. It is common to consider different generationalperspectives in the workplace and its impact on knowledge management andtransfer strategy. This research compares differences in workforce generationsand examines different methods to pass knowledge cross-generationally.Companies must design knowledge transfer strategies conducive tomulti-generational workforce dynamics keeping in mind the generationaldiversity that exists in the workplace. The present study endeavors to provideinsight into this issue.